DEVELOPMENT AND VALIDATION OF NOVEL RP-HPLC-DAD METHOD FOR QUANTIFICATION OF LAPATINIB DITOSYLATE IN NEWER NANO-LIPOSOME FORMULATION: A QUALITY BY DESIGN (QBD) APPROACH - SONAR, PRIYANKA; SHAIKH, KARIMUNNISA; HARER, SUNIL (International Journal of Applied Pharmaceutics, 2022)
Objective: The current study entails quality by design (QbD) enabled the development of a simple, rapid, sensitive, and cost-effective RP-HPLC method for estimation of Lapatinib ditosylate (LPT) in a newly prepared nano-liposomal formulation which has not been reported earlier. Methods: The chromatographic factors were screened using a fractional factorial design. A central composite design was employed as a response surface methodology. Mobile phase ratio, flow rate, and wavelength were identified as critical method parameters. To minimize retention time, peak area and theoretical plates were employed as critical analytical attributes. A novel nano-liposomal formulation of LPT was prepared by the film hydration method. Results: The optimized chromatographic condition was obtained at a mobile phase composition of methanol and 0.05% v/v o-phosphoric acid in water (81:19 v/v), flow rate 0.7 ml/min, and peak detected at wavelength 261 nm using DAD detector. The retention time for Lapatinib was 3.702 min. The developed method was validated as per ICH guidelines ICH Q2 (R1). Linearity (R2= 0.999) was observed in the range of 10-50μg/ml. The limit of detection and limit of quantitation was found to be 0.6309μg/ml and 1.9120μg/ml, respectively. LPT containing liposome formulation assay was found to be 99.03% and %RSD was less than 1%. Conclusion: The newly developed RP-HPLC method applying the QbD approach was found to be simple, specific, precise, accurate, linear, and rugged, with good recovery of LPT in the nano-liposome formulation in a cost-effective manner. Hence it can be employed for the quantification of LPT in bulk and pharmaceutical formulations.